PERAN PEMERINTAH DAERAH MALUKU DALAM PENGELOLAAN KONFLIK SOSIAL - Josephus Noya (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study analyzes the role of the Maluku regional government in managing the social conflict that occurred in the region. The communal conflict that erupted in Maluku from 1999 to 2004 resulted in thousands of casualties and hundreds of thousands of internally displaced persons. This study uses a qualitative approach with a case study method to examine the strategies, policies, and effectiveness of the local government in managing the social conflict. Data were collected through in-depth interviews, field observations, andanalysis of policy documents. The results indicate that the Maluku regional government has implemented various conflict management strategies, including the establishment of interfaith dialogue forums, community reconciliation programs, and the development of socio-economic infrastructure. However, the effectiveness of conflict management still faces challenges related to inter-agency coordination, limited resources, and the complexity of the conflict's root causes. This research contributes to an understanding ofthe dynamics of local conflict and the role of local government in building sustainable peace.